Synthesis and characterization of thermochromic VO₂ nanoparticles and nanothermochromic VO₂-PVP composite coating - Barra, Hamdi Muhyuddin D. (2019)
Vanadium dioxide (VO2) is a promising smart window material because of its thermochromic ability as it transitions from IR-transparent semiconductor to IRreflectant metal at a critical temperature of 68 °C. However, the practical application of VO2 is hindered by some restrictions including low hysteresis or transition strength, high phase transition temperature for near room-temperature applications, low visible transmittance and weak solar modulation ability. Thus, this research was conducted to address these problems. Nanostructured VO2 was prepared by hydrothermal treatment of V2O5-H2C2O4-H2O solution. Various experimental conditions were employed to examine their effects on the resultant nanopowder. X-ray diffraction (XRD) scans of the samples showed that varying synthetic conditions resulted in the selective formation of the metastable B-phase of VO2 from highly pure to polycrystalline that contained the metastable A-phase of VO2 as well as other V-O based compounds such as V6O13 and V4O7. In particular, the sample prepared with a molar ratio of 1:4, fill ratio of 0.63, and hydrothermally synthesized at 180 ºC in 24 hours exhibited narrow and high-intensity peaks belonging exclusively to VO2 (B) indicating high purity and good crystallinity. In addition, field-emission scanning electron microcopy (FESEM) images of the samples revealed the formation of nanorods and nanobelts. Further, the thermochromic and thermodynamically stable M-phase of VO2 was achieved by heating VO2 (B) nanopowder under nitrogen atmosphere. Correspondingly, high purity VO2 (B) resulted into high purity VO2 (M) with improved crystallinity. Also, FESEM images revealed that the VO2 (B) nanobelts and nanorods transformed into spherical, oblate, and platelike shapes after annealing. Meanwhile, differential scanning calorimetry (DSC) measurements showed that VO2 (M) samples exhibited a phase transition temperature of about 66 °C. Subsequently, samples with high purity, good crystallinity and smaller grain size displayed excellent thermochromic properties as indicated by the low hysteresis and high enthalpy. Specifically, it was found that the sample with the best thermochromic characteristics was annealed at a temperature of 650 °C in 2 hours. On the other hand, the addition of tungsten (W) in the synthesis of VO2 resulted in the reduction of the phase transition temperature to as low as 31.64 °C . Moreover, an accompanying increase in the luminous transmittance, solar transmittance and thermal conductivity at room temperature were observed. Additionally, a discernible increase in the thermal conductivity across the phase transition temperature occurred indicating a transition from semiconducting to metallic state. Finally, VO2-PVP composite coating was prepared by dispersing highly pure VO2 nanoparticles onto a glass substrate with polyvinylpyrrolidone as polymeric host matrix. Surface analysis of the sample verified the effective dispersion of nanoparticles onto the substrate. More importantly, the luminous transmittance of the composite samples improved to as high as 86.75%. Indeed, in this work, the phase transition temperature, luminous transmittance, and solar transmittance were simultaneously enhanced which indicate great potential for smart window applications.